Детектор радіосигналу за фазою та амплітудою з використанням AD8302 та ARDUINO - Даценко, О.О.; Свид, І. В. (ХНУРЕ, 2024)
Phase and Amplitude Direction Finder system using two AD8302 integrat- ed circuits and an Arduino microcontroller. By utilizing the AD8302 ICs for measuring signal phase and amplitude, coupled with Arduino for data pro- cessing, the system can effectively locate the source of signals in space. The phase detection involves measuring the phase difference between two antennas placed at a known distance, enabling the determination of signal direction. Through this approach, the system offers simplicity, affordability, and versatili- ty, making it suitable for applications in radar systems, unmanned aerial vehi- cles, and other scenarios requiring precise signal direction identification
Keywords: AD8302; детектор радіосигналу; AD8302